REALPOLITIK AND THE INTERNATIONAL CRIMINAL COURT: RESERVATIONS OF COUNTRIES - Natt, Armaan (Commonwealth Law Review Journal, 2017)
The paper will focus on the term Realpolitik. An attempt will be made to understand the term and highlight the origins of the term from the time of Rochau to its more modern understanding and its present negative connotation. Furthermore the utilization of Realpolitik as a tool of foreign policy by various actors will be highlighted along with its influence on Anglo – American policies. Further there will be a focus on the effect that realpolitik has had on weakening the court, specifically the relationship between the ICC and some of the most powerful countries in the world, namely Russia, China, India and USA. The reservations of each country with the Rome Statute will be discussed. These countries continue to remain outside the jurisdiction of the ICC while wielding considerable influence on it.